Exposure to continuous darkness ameliorates gastric and colonic inflammation in the rat: Both receptor and non-receptor-mediated processes - (:unkn) unknown (WILEY, 2005)
Background and Aim: Melatonin is a hormone involved in the transduction of photoperiodic information, and appears to modulate a variety of neural and endocrine functions. The present study was designed to determine the impact of continuous darkness (CD) on acute gastric and colonic inflammation and the involvement of melatonin receptors in the darkness-related alterations in oxidant gut injury. Methods: Rats were housed either in CD or in standardized light/dark (12/12 h) cycles for 15 days before the induction of colitis or gastric ulcer. Luzindole (MT2 receptor antagonist) was given at a dose of 0.25 mg/kg intraperitoneally 30 min before and 6 and 18 h following the induction of colitis with acetic acid or gastric ulcer with ethanol. Rats were decapitated at 24 h, and the colons and stomachs were removed for macroscopic scoring, histologic assessment and for the determination of tissue malondialdehyde and glutathione levels. Results: All inflammation parameters were increased by acetic acid-induced colitis or ethanol-induced gastric ulcer compared with the control group. Our results indicate that the severity of both gastric and colonic injury is reduced by a 2-week exposure to CD prior to the induction of inflammatory event, while luzindole treatment reversed the protective effect of CD on the colonic and gastric injury. However, darkness-related alterations in malondialdehyde and glutathione levels were not altered by luzindole. Conclusion: Although the CD-induced amelioration of gut injury involves melatonin receptors, the direct antioxidant effects on melatonin appear to be independent of receptor activity. (C) 2005 Blackwell Publishing Asia Pty Ltd.
Keywords: darkness; gastrointestinal inflammation; glutathione; malonaldialdehyde; melatonin; INDUCED COLITIS; PINEAL-GLAND; MELATONIN; ANTIOXIDANT; MODULATION; RHYTHMS; STRESS; CANCER; TRACT